Solamargine Inhibits the Development of Hypopharyngeal Squamous Cell Carcinoma by Decreasing LncRNA HOXA11-As Expression - Meng, Ying; Jin, Mengli; Yuan, Dai; Zhao, Yicheng; Kong, Xiangri; Guo, Xuerui; Wang, Xingye; Hou, Juan; Wang, Bingmei; Song, Wu; Tang, Yong (Frontiers in Pharmacology, 2022)
Hypopharyngeal squamous cell carcinoma (HSCC) is one of the high mortality cancers with a poor prognosis, which is driving the development of new chemotherapeutic agents. We identified the anticancer effects of a natural compound, solamargine (SM), on FaDU cells and explored its mechanism in terms of non-coding RNA. It was observed that SM inhibited the proliferation of FaDU cells with an IC50 of 5.17 μM. High-throughput sequencing data revealed that lncRNA HOXA11-AS was significantly downregulated in cells co-incubated with SM. Further assays demonstrated that SM-induced downregulation of lncRNA HOXA11-AS showed important implications for apoptosis. Given the properties of HOXA11-AS as a miR-155 sponge, we further confirmed that SM upregulated the expression of miR-155 in FaDU cells. C-Myc is a transcription factor that regulates cell differentiation and apoptosis, whose mRNA is considered to be targeted by miR-155. We showed that c-Myc expression was downregulated by SM and accompanied by increased apoptosis, which was consistent with the findings of transcriptome sequencing. Furthermore, SM administration suppressed xenograft tumor growth in a xenograft mouse model in vivo. In the light of the aforementioned findings, our results suggested that SM downregulated the expression of HOXA11-AS, which in turn induces apoptosis by downregulating c-Myc in FaDU, providing evidence for the anticancer effect of SM on HSCC and uncovering the effect of SM on non-coding RNAs as, at least partly, a mechanism of action.